2018
DOI: 10.1038/s41598-018-30851-6
|View full text |Cite|
|
Sign up to set email alerts
|

Low dose of chlorine exposure exacerbates nasal and pulmonary allergic inflammation in mice

Abstract: Work-exacerbated asthma (WEA) is defined as preexisting asthma that worsens with exposure to irritants [e.g., chlorine (Cl2) derivatives] in the workplace. The maximum allowable concentration in the workplace of Cl2 exposure is 3 mg/ m3 (described in OSHA). We investigated in an experimental asthma model in mice the effects of a single exposure to a sodium hypochlorite dose with this allowed chlorine concentration and a tenfold higher dose. Acute chlorine exposure at 3.3 mg/m3 in the OVA-sensitized group incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 72 publications
4
10
0
Order By: Relevance
“…These results demonstrated that inhibition of ROCK2 led to the reduction of mucus and cytokines secretion when CTNNAL1 was silenced. In addition, it has been reported that an increase in ROCK2 leads to mucus hypersecretion,49,50 which confirmed our results.Although ROCK1 and ROCK2 share more than 90% homology in their kinase domains, they had different expression when CTNNAL1 silenced. ROCK1 and ROCK2 might be regulated by different transcription factors when CTNNAL1 silenced.…”
supporting
confidence: 92%
“…These results demonstrated that inhibition of ROCK2 led to the reduction of mucus and cytokines secretion when CTNNAL1 was silenced. In addition, it has been reported that an increase in ROCK2 leads to mucus hypersecretion,49,50 which confirmed our results.Although ROCK1 and ROCK2 share more than 90% homology in their kinase domains, they had different expression when CTNNAL1 silenced. ROCK1 and ROCK2 might be regulated by different transcription factors when CTNNAL1 silenced.…”
supporting
confidence: 92%
“…In high-dose exposure, acids and free radicals damage the cell walls that interact with sulfhydryl groups in amino acids and enzyme systems in the mucosal epithelium. This causes edema, erosion, desquamation, and necrosis of epithelial cells [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, aqueous sodium hypochlorite solution is the most widely used irrigant in endodontic treatment for disinfecting root canals 33 . Exposure to disinfectants based on chlorine products, such as sodium hypochlorite, has been identified as a source of irritation and airway inflammation 34‐36 . In the current COVID‐19 situation, sodium hypochlorite is recommended as effective surface disinfectant 37 .…”
Section: Discussionmentioning
confidence: 99%